Energy Storage: 3D Electronic Channels Wrapped Large‐Sized Na3V2(PO4)3 as Flexible Electrode for Sodium‐Ion Batteries (Small 43/2018). Issue 43 (25th October 2018) - Ni, Qiao; Bai, Ying; Li, Yu; Ling, Liming; Li, Limin; Chen, Guanghai; Wang, Zhaohua; Ren, Haixia; Wu, Feng; Wu, Chuan
Abstract : In article number1702864, Ying Bai, Chuan Wu, and co‐workers design and fabricate hierarchical three‐dimensional electronic channels wrapped large‐sized Na3 V2 (PO4 )3 . As flexible electrode material for sodium‐ion batteries, it exhibits outstanding electrolyte wettability, ultra‐fast electronic conductivity, and high Na ion diffusion coefficients, leading to superior electrochemical performances.